PENENTUAN HARI BAIK DALAM PERKAWINAN DI DESA SAMBIDOPLANG KOTA TULUNGAGUNG - Muhammad Fikri ‘Ainun Najib; Lukman Al-Hakim (Program Studi Komunikasi dan Penyiaran Islam, 2022)
Culture cannot be separated from communication activities, because without cultural communication it will not work well. Culture has been passed down to the next generation from generation to generation and will be connected because of communication or the success of cultural communication. This study aims to describe in detail about the Determination of Good Days in Marriage in Sambidoplang Village, Tulungagung City. The focus of this research is on the communication process and the meaning of symbols that exist in the process of determining auspicious days in marriage. This study uses Clifford Geertz's theory of communication symbols. The method used in this research is the ethnographic method. The use of ethnographic methods will provide a way for researchers to find out in detail about the culture and traditions of the Sambidoplang community of Tulungagung City as the object of the author's research. The results of this study indicate that the communication process in determining a good day before carrying out a marriage is sacred while still carrying out the stages and rituals that must be carried out sequentially. So that gave birth to several symbols of communication, namely verbal and non-verbal. Verbal communication used to interact uses Javanese as the language commonly used by local people and non-verbal communication symbols in every wedding event in the form of traditional rituals that must be carried out. The conclusion from this research is that the people of Sambidoplang Village understand and follow all the stages that are believed to have a good impact on future marriages